A research on acoustical comfort for hearing-impaired individuals in inclusive education places. Issue 1 (March 2021) - Uzeyirli, Zakariyya; Özçevik Bilen, Aslı
The inclusive education method has substantial contributions to hearing-impaired individuals' education and socialization. However, the poor physical environment and acoustic comfort conditions negatively affect speech intelligibility at such places and therefore, the quality of education. Upon determining that there are very few subjective evaluation studies, we conducted a study regarding the impact of acoustic comfort conditions on speech intelligibility at inclusive education places. Within the scope of the study, first, a classroom was determined, and the current acoustic conditions of the class were evaluated objectively by field acoustic measurements. A calibrated model was created in the simulation software of the relevant class and then two more models with optimum reverberation time values of 0.4 s and 0.8 s as suggested in the literature, and auralizations were performed for the models. For subjective evaluation, a subject group of hearing-impaired and normal hearing individuals fulfilling equal conditions were tested by speech discrimination test in real-time in the classroom and from auralization recordings in a laboratory setting. Regarding the results obtained, it was observed that speech intelligibility percentage of normal hearing individuals increased as expected while in hearing-impaired individuals, contrary to the expectations, percentage differed from one another, and there was no increase. Following the discussions with experts, it was concluded that different hearing aids used by hearing-impaired individuals might lead to this situation. Accordingly, it occurs that the possibility to achieve a good speech intelligibility for hearing-impaired individuals even if optimum acoustic values suggested are fulfilled in education places remains unclear.